Motivación y su aporte en el aprendizaje del idioma ingles a los estudiantes de la Unidad Educativa Jaime Roldós Aguilera del Cantón Montalvo, Provincia de Los Ríos - Garrido Morocho, Josue Enrique (2019)
The motivation: it is an attraction towards an objective that supposes an action on the part of the subject and allows to accept the effort required to achieve that objective. The motivation is composed of needs, desires, tensions, discomforts and expectations. Some think that it is the family and social context that distorts motivation as long as it does not value the effort in the acquisition of skills and competencies, which may be partially true. The term motivation refers to the aspect by virtue of which the living subject is a self-dynamic reality that differentiates it from inert beings. The living organism differs from those that are not because it can move itself. Motivation is therefore about those determinants that make the subject behave in a certain way having in himself the principle of his own movement. School motivation is one of the psycho-educational factors that most influence learning. This is not restricted to the application of a particular teaching technique or method, on the contrary, school motivation entails a complex interrelation of various cognitive, affective, social and academic components that are involved.